SHM based on the electromechanical impedance technique with temperature variations: theoretical and experimental approach - Dias, Lorena Lopes [UNESP]; Bueno, Douglas Domingues [UNESP]; Gonsalez-Bueno, Camila Gianini [UNESP] (ABCM, 2023)
To ensure that structures operate within their safety standards and have high performance in operation, an area known as Structural Health Monitoring (SHM) was created. This comprises a set of techniques capable of detecting damage at early stages. In particular, the Electromechanical Impedance (EMI) technique has attracted attention due to its promising results. In general, this technique is most often studied when based on experimental signals, which may limit its physical understanding. However, in recent years, there has been an effort by the scientific community to broaden the understanding of the EMI technique by considering numerical-computational simulations. In this context, the present work investigates the feasibility of an analytical model present in the literature to determine the electromechanical impedance curves of an Euler-Bernoulli beam at different temperatures, since the sensitivity of this technique to temperature variations can lead to incorrect diagnoses in SHM. In this work, a wider temperature range was investigated than the one used in reference literature. A numerical and experimental approach was employed. The theoretical and experimental results obtained for different temperatures are in close agreement with each other, especially regarding the position of EMI peaks.
SHM baseado na técnica de impedância eletromecânica com variações de temperatura: abordagem teórica e experimental
Keywords: Structural Health Monitoring; Electromechanical Impedance; Temperature; Analytical Model; Experimental Data